The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1055/s-0042-1750851
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy: Principles, Science, and Patient Selection in Neurology

Abstract: Cognitive behavioral therapy (CBT) is a widely used therapeutic modality in general psychiatric practice. In this review, we consider its application to neurological disorders. We examine the basic framework of CBT—that symptoms, emotions, thoughts, and behaviors are all interrelated and that therapeutic interventions that lead to change in thoughts or behavior may have the potential to reduce symptoms or emotional distress. We also outline specific methodological issues to consider when reading or planning st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…CBT is a psychosocial intervention aimed at reducing symptoms of various mental health conditions, primarily depression and anxiety disorders (Raggi et al ., 2007; Panerai et al ., 2016; Carson and McWhirter, 2022). CBT focuses on challenging and changing cognitive distortions, such as thoughts, beliefs, and attitudes, along with their associated behaviors.…”
Section: Treatmentmentioning
confidence: 99%
“…CBT is a psychosocial intervention aimed at reducing symptoms of various mental health conditions, primarily depression and anxiety disorders (Raggi et al ., 2007; Panerai et al ., 2016; Carson and McWhirter, 2022). CBT focuses on challenging and changing cognitive distortions, such as thoughts, beliefs, and attitudes, along with their associated behaviors.…”
Section: Treatmentmentioning
confidence: 99%
“…124 It is worth mentioning that, even prepandemic, stress and adverse mental health were associated with inflammation and neuroinflammation, making the direction of causality difficult to determine. 8,[125][126][127][128][129] Brusaferri et al found in pandemic patients without having had COVID-19, "novel evidence of elevated neuro-inflammatory markers in cortical and subcortical regions . .…”
Section: Long-pandemic Effectsmentioning
confidence: 99%
“…150,152 Treatment suggestions are similar to SSD in general, focusing on explanation and education, physical therapy/rehabilitation, and cognitive behavioral therapy (aiming to change maladaptive thoughts and behaviors). 127,145 An older study is particularly interesting. 153 Of those suffering from environmental hypersensitivity disorder, 90% reported suffering from at least one other so-called "fashionable" (i.e., media popularized) condition, including food allergy, candidiasis hypersensitivity, post-infectious neuromyasthenia, fibrositis, and temporomandibular joint syndrome.…”
Section: Related Disorders (Syndromes)mentioning
confidence: 99%
See 2 more Smart Citations